Development of colorimetric RT-LAMP for rapid visual detection of SARS-CoV-2 in clinical samples / Adibah Che Mohamad Nor - Che Mohamad Nor, Adibah (2024)
COVID-19 outbreak caused by the novel coronavirus SARS-CoV-2 has forced an urgent need for robust testing strategies to curb the spread of the disease. This study aims to develop, optimize and validate a convenient, yet reliable colorimetric RTLAMP assay for rapid visual detection of COVID-19. Six newly designed LAMP primers were screened in a singleplex RT-LAMP assay to target on the highly conserve region of nucleocapsid gene (N gene), envelope gene (E gene), open reading frame 1ab (ORF1ab) gene and RNA dependent RNA polymerase (RdRp) gene of SARS-CoV-2, individually. Following optimization, N3 primers presented as the optimal primer based on its amplification performance and colour contrast between negative and positive result. Further study was proceeded with colorimetric RTLAMP assay using N-3 primers alone. The optimised protocol of the developed assay using N-3 primers represented a limit of detection (LOD) as low as 5 copies of DNA plasmid control in a 12.5 μl reaction within 30 minutes of incubation. However, in real clinical samples, the assay took about 35 minutes of incubation to give yield to positive result. Hence, final optimal reaction condition for N3 primers targeting the N gene was decided at 65oC for 35 minutes of incubation. In total, the assay took approximately 59 minutes combining 23 minutes of RNA extraction with 35 minutes of isothermal amplification reaction and 1 minutes of direct colorimetric observation. As evidence of high specificity, no cross-reactivity was detected when testing the assay against other non-SARS-CoV-2 viruses, while BLAST analysis proven the low chances of cross-reactivity against most viruses studied. In clinical validation, the developed colorimetric RT-LAMP assay recorded a high degree of sensitivity and specificity at 80.25% and 94.12%, respectively, when tested on 183 purified RNA samples with concordance rate of 87.98% to qRT-PCR assay as the standard reference method. For the conclusion, this assay provides a simple, rapid (less than an hour) yet reliable approach that enables visual detection of SARS-CoV-2 N gene using newly designed primers in molecular diagnosis for a cost-effective COVID-19 prevention and control strategies.